Cation‐enhanced capillary electrophoresis separation of atropoisomer anions. Issue 23 (7th October 2015) - Na, Yun‐Cheol; Berthod, Alain; Armstrong, Daniel W.
Abstract : CE was used to study the separation of the atropoisomers of four phosphoric acids and two sulfonic acids and the enantiomers of two phosphoric acids. All solutes are in their anionic forms in aqueous electrolytes. The chiral additives were two hydroxypropyl cyclodextrins (CDs) and cyclofructan 6 (CF6). The CDs were able to separate four solutes and the CF6 additive could separate only one: 1, 1′‐binaphthyl‐2, 2′‐diyl hydrogenphosphate (BHP). Since CF6 is able to bind with cations, nitrate of alkaline metals, Ba 2+, and Pb 2+ were added, greatly improving the BHP separation at the expense of longer migration times. There seems to be a link between CF6–cation‐binding constants and BHP resolution factors. Cation additions were also performed with CD selectors that are less prone to form complexes with cations. Significant improvements of enantiomer or atropoisomer separations were observed also associated with longer migration times. It is speculated that the anionic solutes associate with the added cations forming larger entities better differentiated by CDs.